Functional characterization of extrinsic tongue muscles in the Pink1-/- rat model of Parkinson disease - Glass, Tiffany J. (PLoS One, 2020)
Parkinson disease (PD) is associated with speech and swallowing difficulties likely due to pathology in widespread brain and nervous system regions. In post-mortem studies of PD, pathology has been reported in pharyngeal and laryngeal nerves and muscles. However, it is unknown whether PD is associated with neuromuscular changes in the tongue. Prior work in a rat model of PD (Pink1-/-) showed oromotor and swallowing deficits in the premanifest stage which suggested sensorimotor impairments of these functions. The present study tested the hypothesis that Pink1-/- rats show altered tongue function coinciding with neuromuscular differences within tongue muscles compared to wildtype (WT). Male Pink1-/- and WT rats underwent behavioral tongue function assays at 4 and 6 months of age (n = 7–8 rats per group), which are time points early in the disease. At 6 months, genioglossus (GG) and styloglossus (SG) muscles were analyzed for myosin heavy chain isoforms (MyHC), α-synuclein levels, myofiber size, centrally nucleated myofibers, and neuromuscular junction (NMJ) innervation. Pink1-/- showed greater tongue press force variability, and greater tongue press forces and rates as compared to WT. Additionally, Pink1-/- showed relative increases of MyHC 2a in SG, but typical MyHC profiles in GG. Western blots revealed Pink1-/- had more α-synuclein protein than WT in GG, but not in SG. There were no differences between Pink1-/- and WT in myofiber size, centrally-nucleated myofibers, or NMJ innervation. α-synuclein protein was observed in nerves, NMJ, and vessels in both genotypes. Findings at these early disease stages suggest small changes or no changes in several peripheral biological measures, and intact motor innervation of tongue muscles. Future work should evaluate these measures at later disease stages to determine when robust pathological peripheral change contributes to functional change, and what CNS deficits cause behavioral changes. Understanding how PD affects central and peripheral mechanisms will help determine therapy targets for speech and swallowing disorders.